Postural influences on the mechanical and neural components of the cardiovagal baroreflex. (22nd March 2013) - Taylor, C. E.; Willie, C. K.; Atkinson, G.; Jones, H.; Tzeng, Y.‐C.
Abstract Aim The ability to maintain arterial blood pressure when faced with a postural challenge has implications for the occurrence of syncope and falls. It has been suggested that posture‐induced declines in the mechanical component of the baroreflex response drive reductions in cardiovagal baroreflex sensitivity associated with postural stress. However, these conclusions are largely based upon spontaneous methods of baroreflex assessment, the accuracy of which has been questioned. Therefore, the aim was to engage a partially open‐loop approach to explore the influence of posture on the mechanical and neural components of the baroreflex. Methods In nine healthy participants, we measured continuous blood pressure, heart rate, RR interval and carotid artery diameter during supine and standing postures. The modified Oxford method was used to quantify baroreflex sensitivity. Results In response to falling pressures, baroreflex sensitivity was similar between postures (P = 0.798). In response to rising pressures, there was an attenuated (P = 0.042) baroreflex sensitivity (mean ± SE) in the standing position (−0.70 ± 0.11 beats min−1 mmHg−1) compared with supine (−0.83 ± 0.06 beats min−1 mmHg−1). This was explained by a diminished (P = 0.016) neural component whilst standing (−30.17 ± 4.16 beats min−1 mm−1) compared with supine (−38.23 ± 3.31 beats min−1 mm−1). These effects were consistent when baroreflex sensitivity was determined using RR interval. Conclusion Cardiovagal baroreflex sensitivity in response to rising pressures is reduced in young individuals during postural stress. Our data suggest that the mechanical component is unaffected by standing, and the reduction in baroreflex sensitivity is driven by the neural component.